2010
DOI: 10.1021/es101535f
|View full text |Cite
|
Sign up to set email alerts
|

Radioadaptive Response Induced by Alpha-Particle-Induced Stress Communicated in Vivo between Zebrafish Embryos

Abstract: We report data demonstrating that zebrafish embryos irradiated by alpha particles can release a stress signal into the water, which can be communicated to the unirradiated zebrafish embryos sharing the same water medium and thereby inducing a radioadaptive response in these unirradiated zebrafish embryos. The effects of radiation on the whole embryos were studied through quantification of apoptotic signals at 24 h post fertilization through staining with the vital dye acridine orange, followed by counting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…The strength of the rescue effect depends on the number of rescuing unirradiated bystander embryos [33], [34], [35]. Based on these studies, radioadaptation experiments were done on embryonic ZF4 cells (see Figure 6 for experimental set up).…”
Section: Resultsmentioning
confidence: 99%
“…The strength of the rescue effect depends on the number of rescuing unirradiated bystander embryos [33], [34], [35]. Based on these studies, radioadaptation experiments were done on embryonic ZF4 cells (see Figure 6 for experimental set up).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using the zebrafish model system to evaluate ionizing radiation exposure have been used to assess general toxicity (e.g., mortality, hatching rates, gross morphological alterations, DNA damage, and apoptosis) (e.g., Bladen et al, 2007; Choi et al, 2010a,b, 2012a, 2013; Pereira et al, 2011; Sorrells et al, 2012; Yu et al, 2012; Toruno et al, 2014), to screen radiation protectors (McAleer et al, 2005; Geiger et al, 2006), and to assess the long-term effects on liver gene expression (Jaafar et al, 2013). To the best of our knowledge, no work is published on the effect of IR to heart rate using the zebrafish model.…”
Section: Discussionmentioning
confidence: 99%
“…Yum et al [215] reported the communication of alpha-particle-induced bystander signals between 1.5 hpf zebrafish embryos. Choi et al [229,230] further demonstrated that the RIBE communication between zebrafish embryos in vivo could actually induce the RAR against a challenging dose and induce a hormetic effect, respectively, in partnered unirradiated zebrafish embryos sharing the same medium with irradiated embryos. Moreover, unirradiated bystander zebrafish embryos were found to release a feedback signal back to the irradiated zebrafish embryos, which lead to a mitigation of the effects of radiation in the irradiated embryos [231].…”
Section: Conclusion and Discussionmentioning
confidence: 99%